2020
DOI: 10.1101/2020.05.29.20109199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic effectiveness of interferon-alpha 2b against COVID-19: the Cuban experience

Abstract: Background Effective therapies are needed to control the SARS-Cov-2 infection pandemic and reduce mortality associated with COVID-19. Several clinical studies have provided evidence for the antiviral effects of type I interferons (IFNs) in patients with respiratory coronaviruses. This study assessed the therapeutic efficacy of IFN-alpha 2b in patients infected with SARS-CoV-2 during the first month after the outbreak began in Cuba. Method This multicenter prospective observational study was conducted in 16 hos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…One prospective cohort study [64] enrolled 814 patients with COVID-19 in Cuba. Seven hundred sixty-one were treated with the IFN-α2b (intramuscular injection, 3 million IU 3 times per week, for 2 weeks) combined with the approved protocol (included lopinavir-ritonavir and chloroquine), 53 received the protocol without IFN treatment.…”
Section: Implementation Considerationmentioning
confidence: 99%
“…One prospective cohort study [64] enrolled 814 patients with COVID-19 in Cuba. Seven hundred sixty-one were treated with the IFN-α2b (intramuscular injection, 3 million IU 3 times per week, for 2 weeks) combined with the approved protocol (included lopinavir-ritonavir and chloroquine), 53 received the protocol without IFN treatment.…”
Section: Implementation Considerationmentioning
confidence: 99%
“…In addition, two studies consistently demonstrated opposite associations between Type I interferon therapy and clinical outcomes, [30,33] when comparing summary statistics and other included studies. [28,29,31,34,35] Heterogeneity among populations studied may play a role in the disparate individual results, as half of these studies were conducted in China, one was conducted in Iran, five were conducted in Western Europe, and one was conducted in Cuba. Other irreconcilable factors that may have influenced patient outcomes included individual study exclusion criterion, as well as the dosage and delivery method of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of 3 sets of studies with 990, 454, and 1480 patients receiving Type I interferon therapy revealed that there were no significant associations between receiving Type I interferon therapy, compared to standard of care, and ICU admittance, requiring mechanical ventilation, or developing a severe or critical case of COVID-19, respectively (p>0.05; Figure 3B; Figure 3C; Figure 3D). [28][29][30][31][32][33][34][35][36] The analyses included 97, 167, and 537 control patients, respectively. The data exhibited very high heterogeneity in cases of ICU admittance and disease severity (both I 2 >90%), but relatively low in the case of mechanical ventilation (I 2 =12%).…”
Section: Effect Of Interferon Therapy On Clinical Outcomes In Covid-19mentioning
confidence: 99%
“…The proportion of fully recovered patients was respectively as 95.4% versus 26.1%, p<0.01). The CFR was 0.92 versus 2.95% [97]. Another exploratory study reported IFN treatment on accelerated viral clearance and reductions in circulating IL-6 and CRP levels among 77 patients after adjusting for age, sex, and co-morbidities [98].…”
Section: Interferon (Ifn) Beta-1a (Also Known As Ifn Beta 1-alpha)mentioning
confidence: 98%